The Inhibitory Potential of Strawberry (Fragaria x ananassa) Extract Against Staphylococcus aureus: Implications for Dental Caries Prevention - Haria Fitri; Reno Wiska Wulandari; Nabila Jihan Yandika (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Dental caries is a prevalent oral health issue globally, and Staphylococcus aureus is a key pathogen involved in its development. Strawberry fruits, known for their medicinal properties, contain bioactive compounds with potential antibacterial effects. This study aimed to investigate the inhibitory potential of strawberry extract against S. aureus. Methods: A laboratory experimental study was conducted using a post-test-only control group design. Varying concentrations (10%, 15%, 20%, 25%) of strawberry fruit extract were prepared. The antibacterial activity was assessed using the disc diffusion method against S. aureus. Distilled water served as a negative control. The diameter of inhibition zones was measured after 24 hours of incubation at 37°C. Results: Strawberry fruit extract demonstrated inhibitory effects on the growth of S. aureus at concentrations of 15%, 20%, and 25%. The average inhibition zone diameters were 0.54 mm, 2.30 mm, and 3.00 mm, respectively. No inhibition was observed at 10% concentration or with the distilled water control. Conclusion: Strawberry fruit extract exhibits potential as an antibacterial agent against S. aureus, suggesting its possible application in dental caries prevention. Further research is needed to explore its clinical efficacy and identify the specific bioactive compounds responsible for the observed antibacterial activity.